Stella Maris [compact disc, unabridged] - McCarthy, Cormac, 1933- (Penguin Random House, 2022)
Alicia Western, a doctoral candidate and paranoid schizophrenic, admits herself to the hospital. There, she refuses to talk about her brother. Instead, she contemplates madness and perceived experience.